Optimized Power Allocation for Cooperative Amplify-and-Forward with Convolutional Codes - N Nasaruddin; M Melinda; E Elizar (Institute of Advanced Engineering and Science, 2014)
Future wireless communications technology should fulfill the demands of multimedia applications, interactive internet service, high data rates and power efficiency. However, wireless channel is affected by multipath fading that can degrade the system performance. To overcome the problem, cooperative communication has been introduced to be an efficient diversity technique to combat the multipath fading, to improve capacity and the system performance, and to reduce the energy comsumption by using power allocation technique in the network. This paper proposes an optimized power allocation (OPA) for cooperative amplify-and-forward (AF) protocol with convolutional codes (CC). A computer simulation model for the proposed system is developed using Matlab programming. Then, performance of the system is evaluated in terms of the system throughput, bit error rate and amplification coeficient for power allocation. Furthermore, the different rates of CC are also considered in the network. Simulation results show that multi-relay AF network can provide a higher throughput and lower bit error rate. Moreover, the performance of OPA system is better than that of non-OPA system. The using lower rate of CC in the OPA system provides coding gain for multi-relay cooperative AF network. Finally, the different amplification coeficients among relays give a significant improvement to optimize the system performance.